Universally composable secure trusted access protocol for WLAN Mesh networks - MA Zhuo1; MA Jian-feng1; ZENG Yong1; SHEN Yu-long1 (Tongxin xuebao)
The current access protocols of WLAN Mesh network and trusted network could not satisfy the requirements of performance and security when the trusted access is needed in WLAN Mesh networks.Then,a provably secure trusted access protocol MN-TAP for the WLAN Mesh networks was proposed.Such protocol will achieve authentication and key confirmation among the access requestor,policy enforcement point and policy decision point.At the same time,the protocol could realize the platform authentication and platform integrity verification in the first round of protocol interaction,which would improve the efficiency of the protocol and decrease the overhead of the servers.A provably secure model was used,named universally composable secure model,to analyze the security of the protocol.And the performance of the protocol was analyed.The results show that: the protocol is a UC-secure protocol,and the performance has great advantages over the current protocols.